Familial Eosinophilic Granulomatosis with Polyangiitis in a Sister and Brother - Ueki, Yuriko (Intern Med, 2019)
Eosinophilic granulomatosis with polyangiitis (EGPA) is a vasculitis characterized by an abnormally high number of eosinophils in the peripheral blood and tissues. EGPA is an extremely rare disorder, with an incidence of 0.5 to 3.7 new cases per million people per year and an overall prevalence of 2.4 to 14 per million adults. There is little knowledge about the genetic factors that influence this disease. There are only two reports of familial EGPA: one in Japan and one in Turkey. We herein report a third case of familial EGPA in a brother and sister who were negative for myeloperoxidase-antineutrophil cytoplasmic antibodies.